2015
DOI: 10.1186/s12883-015-0383-4
|View full text |Cite
|
Sign up to set email alerts
|

Misdiagnosed murine typhus in a patient with multiple cerebral infarctions and hemorrhage: a case report

Abstract: BackgroundRickettsias cause a wide spectrum of tick-, flea-, or mite-borne infections. Rickettsial infections have no classical manifestations and can often lead to encephalitis, which can be fatal if improperly diagnosed.Case presentationA 74-year-old male farmer was admitted to the hospital with fevers and a headache that had lasted for 10 days, followed by 4 days of unconsciousness, and his condition continued to deteriorate. Images showed multiple acute lesions in the brain stem, and bilateral cerebral and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 11 publications
(11 reference statements)
0
4
0
Order By: Relevance
“…In addition to the Laotian study, other studies of MT have reported seizures, 20,29,38,39 which were ascribed to hyperpyrexia, intracranial hemorrhage, and hypoglycemia. 29 Other CNS manifestations that have been reported in MT include: hearing loss 40,41 ; encephalitis with white matter infarctions, and intracerebral and subarachnoid hemorrhages 42 ; cerebellitis with ataxia and tremors 43 ; intracranial hemorrhage 29 ; hemiparesis 10 ; cranial nerve palsies 26,[44][45][46] ; ataxia 38,47 ; behavioral alterations; and neurocognitive deficits 20,31,48 and pseudotumor cerebri. 20 Nevertheless, in most MT patients, the CNS manifestations resolve after the patient defervesces.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the Laotian study, other studies of MT have reported seizures, 20,29,38,39 which were ascribed to hyperpyrexia, intracranial hemorrhage, and hypoglycemia. 29 Other CNS manifestations that have been reported in MT include: hearing loss 40,41 ; encephalitis with white matter infarctions, and intracerebral and subarachnoid hemorrhages 42 ; cerebellitis with ataxia and tremors 43 ; intracranial hemorrhage 29 ; hemiparesis 10 ; cranial nerve palsies 26,[44][45][46] ; ataxia 38,47 ; behavioral alterations; and neurocognitive deficits 20,31,48 and pseudotumor cerebri. 20 Nevertheless, in most MT patients, the CNS manifestations resolve after the patient defervesces.…”
Section: Discussionmentioning
confidence: 99%
“…Murine typhus is often a mild illness but can become more severe in refugee camps ( 18 ), and fatal and severe CNS cases of murine typhus have been described ( 14 , 19 , 20 ). Murine and epidemic typhus can be discerned neither histopathologically nor clinically (except perhaps by their expected respective severities and associated mortality rates, the presence of vectors, or flea or louse bite reactions on the skin).…”
Section: Discussionmentioning
confidence: 99%
“…Unbiased diagnostic tools such as metagenomic next-generation sequencing, which is becoming more and more accessible, might have helped to identify the pathogen more rapidly [ 13 ]. Vasculitic complications are common but rarely documented to the extent reported in our patient [ 14 , 15 ]. Consistent with other case series, the initial response to antibiotic therapy was good.…”
mentioning
confidence: 89%